Scenario analysis for shipping investment strategies - Xu, Yiming. (2013)
Investment is an activity to set current commitment to derive future incomes. The cyclical nature of the shipping industry and huge amounts of capital involved forebode a high degree of uncertainty in decision-making for ship investment.